Identification of Micro-organisms (Parasites and Bacteria) which are Potential as Pathogenic Agent in Glass Eel of Anguilla spp. at the Eel Capture Location, Sukabumi, West Java - Dandy E. Prasetiyo; Taukhid Taukhid Taukhid; Septyan Andriyanto; Muhammad Azril; Nur Ahyani; Selia Hermawati; Amriana Amriana (Journal of Aquaculture Science, 2021)
Eel (Anguilla sp.) is one of the important commercial fish in some countries particularly in East Asian countries such as Japan, South Korea, China, and Taiwan. The need of eel fry or frequently called as glass eel still relies on the natural capture. The issue of natural captured fish is the high level of bacterial infections and diseases. The dependence of glass eel from the nature provides an indication of infections of parasites and bacteria in glass eel. The existence of parasites and bacteria as microorganisms which are potential as pathogenic agents in the cycle of eel culture can be a serious obstacle, so that the glass eel handling needs a particular attention since the capturing proses from the nature. Therefore, identification of parasites and bacteria in the capture location of glass eel was necessarily conducted in Pelabuhan Ratu Bay, Sukabumi, West Java. The glass eel sampling was conducted in May-June 2019, in 3 locations of estuary with the highest capture yield namely Cimandiri River, Cikaso River and Cibuni River. The number of samples taken were 30 eels at each river location with 2 replicates, so that the total eel samples which were taken were 180 eels. Identification of parasites was conducted by examination of ectoparasite and endoparasite and dentification of bacteria was conducted by conventional method (biochemical method). Based on the result of identification, there was no parasite found in the glass eel samples, while bacteria found as many as 12 species and 3 dominant species namely Listeria sp. found in 40 eel samples with prevalence of 22.2%, Aeromonas hydrophila found in 28 eel samples with prevalence of 15.6%, and Staphylococcus spp. found in 22 eel samples with prevalence of 12.2%.Keyword : Micro-organism, Pathogen, Glass Eel, Anguilla spp.